2022
DOI: 10.1016/j.energy.2021.122015
|View full text |Cite
|
Sign up to set email alerts
|

A multi-disciplinary approach to estimate the medium-term impact of COVID-19 on transport and energy: A case study for Italy

Abstract: The aim of this paper is to estimate the potential impacts of different COVID-19 scenarios on the Italian energy sector through 2030, with a specific focus on transport and industry. The analysis takes a multi-disciplinary approach to properly consider the complex interactions of sectors across Italy. This approach includes the assessment of economic conditions using macroeconomic and input-output models, modelling the evolution of the energy system using an energy and transport model, and forecasting the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Interestingly, studies in different European nations reveal a strong character relating to the typical behaviours of each population, meaning that gathering data specific to Wales or UK could be informative for future policy or planning. Bazzana et al (2022) predominantly reported the impact of lockdown, not remote working. However, they did indicate that at the height of the 'stay-at-home', or 'social distancing' regulations in May 2020, GHG emissions in Italy decreased by 26%, on average.…”
Section: Bottom Line Results For Energymentioning
confidence: 99%
“…Interestingly, studies in different European nations reveal a strong character relating to the typical behaviours of each population, meaning that gathering data specific to Wales or UK could be informative for future policy or planning. Bazzana et al (2022) predominantly reported the impact of lockdown, not remote working. However, they did indicate that at the height of the 'stay-at-home', or 'social distancing' regulations in May 2020, GHG emissions in Italy decreased by 26%, on average.…”
Section: Bottom Line Results For Energymentioning
confidence: 99%
“…Positive projections anticipated a drop in energy demand. Numerous studies revealed that government restrictions lowered energy use; hence, demand will increase to pre-epidemic levels [8] . Based on its short-term and long-term effects on energy demand, the pandemic has long-lasting effects.…”
Section: Discussion: Post-covid-19 Era and Policy Recommendationsmentioning
confidence: 99%
“…Cvetkovic et al [106] analyzed people's energy consumption behavior during the pandemic and used EnergyPlus software for the simulation of the consumption of electricity, natural gas and water in a few residential houses in Serbia. Bazzana et al [35] tried to measure the possible effect of the COVID-19 pandemic to the energy sector in Italy. The authors applied a multidisciplinary approach and created different scenarios in order to forecast market reactions and energy consumption.…”
Section: Impact On Consumption and Habitsmentioning
confidence: 99%